[U(Tp(Me2))2(bipy)]+: a cationic uranium(III) complex with single-molecule-magnet behavior - Antunes, Maria A; Pereira, Laura C J; Santos, Isabel C; Mazzanti, Marinella; Marçalo, Joaquim; Almeida, Manuel (Inorganic chemistry, 2011)
The addition of 2,2'-bipyridine to [U(Tp(Me2))(2)I] (1) results in the displacement of the iodide and the formation of the cationic uranium(III) complex [U(Tp(Me2))(2)(bipy)]I (2). This compound was isolated as a dark-green solid in good yield and characterized by IR and NMR spectroscopies, and its molecular structure was determined by single-crystal X-ray diffraction. Studies of its magnetic properties revealed a frequency dependence of magnetization with a blocking temperature of 4.5 K and, at lower temperatures, a slow relaxation of magnetization with an energy barrier of 18.2 cm(-1), characteristic of single-molecule-magnet behavior.